Intonation of Interrogative Sentences in Learning Arabic for Mahārat al-Kalām - Sri Utami; Irfan Hania; Yuli Imawan; Nada Nabilah Syafiqoh; Suteja; Faiqotussana (Universitas Negeri Jakarta, 2023)
The purpose of this study was to find out the intonation patterns of interrogative sentences for students in class 10 of MAS Al-Hikmah, Soe, Nusa Tenggara Timur, their acceptance by Arabic linguists, and their learning of speaking skills (mahārat al-kalām). This research is a case study that is included in qualitative descriptive research. The data collection technique in this study was to test the intonation of interrogative sentences with the help of the Praat application. The data were analyzed with qualitative descriptive and investigative methods. The results obtained are: first, students of class 10 at MAS Al-Hikmah can apply intonation patterns of Arabic interrogative sentences with varying acceptability values, assisted by teaching aids in the form of articulated sound images and contours. Second, apply the application of interrogative sentence intonation patterns to learning mahārat al-kalām, namely, students and lecturers as parties involved in this learning can apply the principles and fulfill the components of learning Arabic in general.